Ultrasonography in Gynecology - Rizk, Botros R. M. B.; Puscheck, Elizabeth E. (Cambridge : Cambridge University Press, 2014)
Ultrasonography is a cornerstone in the evaluation of gynecologic disease. This authoritative new book looks at the techniques of ultrasonography in both office and hospital settings, offering guidance on the optimal use of equipment and covering the full range of benign and malignant gynecologic disease as well as infertility. Ultrasonography in Gynecology offers extensive coverage of the diagnostic potential of ultrasound in gynecologic disease, from the moment the patient walks into the physician's office. All the different approaches in the ultrasonographic evaluation of disease - including 3D ultrasonography, 3D sonohysterography, Doppler imaging and pelvic floor imaging - are extensively covered, with color images throughout. Written and edited by leaders in the field of ultrasonography who have actively participated in national and international teaching courses, Ultrasonography in Gynecology is a must for all gynecologists dealing with infertility, endometriosis, uterine fibroids, gynecologic cancers, and many more gynecologic conditions.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Ultrasonics in obstetrics